ANALISIS YURIDIS HAK WARIS TERHADAP ANAK ANGKAT DALAM HUKUM ADAT BATAK SIMALUNGUN - Maurice Rogers; Herdi Munte; Johannes Eka Pratama Jawak (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
To be able to meet the legal needs of the Indonesian people in the present and the future in the context of building a just and prosperous society based on Pancasila and the 1945 Constitution, it is necessary for the drafting of national law to have conceptions and legal principles derived from customary law. Customary law is one of the important sources to obtain materials for the development of national law leading to legal unification, which will mainly be implemented through the making of laws and regulations. The type of research used in the field review is empirical law and literature review or often referred to as normative law where both are mutually sustainable in the preparation of the final lecture. In this case, inheritance law is the law that regulates the transfer of wealth left by someone who dies and the consequences for his heirs. The formulation of the problem that the researcher describes in this thesis is about the position of adopted children in Simalungun customary law, in terms of the distribution of inheritance to adopted children in the Simalungun Batak customary law and the procedures for the distribution of inheritance in the patrilineal system to adopted children in Simalungun Batak customs. The position of adopted children in the Simalungun customary law, namely the adoption of children in Indonesia is known as adoption where in the Simalungun Batak custom it is called Ngampu Anak. In this case, the position of the adopted child is the same as that of the biological child, where the adopted child goes through a strong customary and legal process. The division of inheritance to adopted children in the Simalungun Batak customary law, namely the rights of stepchildren or adopted children can be equated with the rights of biological children. Because before a child is adopted or adopted, must go through a certain customary process. Which aims that the person is legally legally the clan of the person who raised him. However, there are certain types of assets that cannot be passed on to stepchildren and adopted children, namely family inheritance. The legal consequences of adopting a child between an adopted child and adoptive parents as well as an adopted child and biological parents are against an adopted child. Generally, the adoption of a child results in the transfer of the position of the child from the family environment of the original parent to the family environment of the adoptive parent. The adopted child becomes a member of the adoptive parent's family.